ABOUT POETESS ZULFIYA’S POEMS - Abralova, Nafisa (Educational Research in Universal Sciences, 2023)
This article presents information about the life and work of the poet Zulfiyakhanim, samples of his poems are given. More emphasis is placed on the subject of his poems, on aspects of meaning.